A special issue on nanomedicine in Latin America - Abraham, Gustavo Abel (2013)
This special issue of Journal of Biomaterials and Tissue Engineering includes articles from Latin American researchers that work in an emerging discipline at the interface of biomaterials science, nanotechnology and therapeutics called Nanomedicine and that comprises the use of different mono, bi and three-dimensional nano-objects (e.g., nanoplates, nanoparticles, nanotubes, etc.) to address different medical problems. A peculiarity of Nanomedicine is its pivotal role in the articulation of different complementary research disciplines such as pharmaceutical technology (aimed to develop drug dosage forms) and bioengineering (aimed to engineer medical devices without pharmacological, immunological or metabolic activity). Undoubtedly, the use of nano-objects to execute controlled functions in the health field is blurring frontiers among disciplines that were well defined until very recent times. In this very dynamic scenario, the social and economic impact of Nanomedicine has to be undertaken by a scientific community that envisages and fully understands the profound consequences of its intervention in living beings. Unfortunately, a misinterpretation of the scope encompassed by Nanomedicine made at first glance in Latin America gave access almost exclusively to chemistry and physics experts. This vision restricted the involvement of biomedical researchers in the nanotechnology arena and, as a result of this phenomenon, most of the Latin American countries and particularly Argentina, delayed the local development of the nanomedicine education programs and scientific platforms. The foundation of any emerging applied research field demands the strategic investment of extensive governmental funds and the consequent generation of a critical mass of young, motivated and highly-qualified scientists that will later develop powerful and versatile technological platforms and educate a next generation of scientists. Hence, to push the field forward, in 2010, we founded the Argentine Society for Nanomedicines (NANOMED-ar). One of the urgent issues to be addressed in Latin America is the absence of a public health agenda focused on Nanomedicine; priority research lines and disease-oriented research projects have not been identified yet. In Argentina, the critical mass of nanomedical scientists remains relatively small and most of the activities are concentrated by a few highly qualified research groups in public institutions distributed across the country. These research groups own solid expertise, know-how and nanotechnology platforms in areas such as (i) synthesis, modification and characterization of polymeric and non-polymeric carriers; (ii) design and development of drug delivery implants; (iii) encapsulation, release and targeting of drugs, genes and vaccines and (iv) development of standard and innovative pharmaceutical formulations and in vitro and preclinical studies, among others.